Safety Assessment Method for Heavy-Cargo Transportation on Bridges in Service - Li, Guangqi; Zhang, Xingyuan; Wang, Haicheng (Transactions on Engineering and Technology Research, 2024)
In order to accurately evaluate whether large transport vehicles can safely pass the bridge on the transport route, the load effect comparison method and the actual load checking calculation method are introduced, and the safety assessment of a prestressed continuous small box girder bridge is analyzed with a case study. The results show that using the load effect comparison method can not distinguish whether large vehicles have the right of way. Based on the actual load checking method, it is found that the flexural capacity of the combined effect of the structure and the maximum and minimum stress under normal use meet the design requirements, and the large vehicle with a total weight of 755t meets the traffic requirements.